Nematode parasites of two species of Chaunus (Anura: Bufonidae) from Corrientes, Argentina - Elizabeth, Cynthya Elizabeth; Hamann, Monika Inés (Zootaxa, 2007)
From October 2000 to February 2005, the nematofauna of Chaunus fernandezae (Gallardo, 1957) and Chaunus bergi (Céspedez, 2000) was studied from Corrientes city, Province of Corrientes, Argentina. Twenty one C. fernandezae (81.0%) and fifteen C. bergi (75.0%) were parasitized. Four nematodes species were found. Chaunus fernandezae is a new host for Ortleppascaris sp., Physaloptera sp., Cosmocerca podicipinus and C. parva. Chaunus bergi a new host for C. podicipinus and C. parva.